Digital Teaching Competence in Initial Training: Case Studies from Chile and Uruguay [a Competência Digital Do Professor Em Formação Inicial: Estudo a Partir Dos Casos Do Chile E Uruguai] [la Competencia Digital Docente en Formación Inicial: Estudio a Partir de Los Casos de Chile y Uruguay] - Silva-Quiroz, J; Miranda-Rozas, P (Arizona State University, 2019)
At present, it is essential for teachers to develop digital competence (DCT), starting at their initial training, to properly use Information and Communication Technologies (ICTs) in their daily practices, in addition to promoting DCT in the students. This article presents the main results of a comparative DCT study in last year pedagogy students in Chile and Uruguay. A mixed methodology was used to design and validate a test-type instrument with experts, which presented the use of ICTs in teaching contexts. This methodology enabled assessing DCT at four levels of dimensions with 10 indicators. The instrument was applied to a stratified representative sample with 5% margin of error made up of 568 pedagogy students, 273 from Chile and 295 from Uruguay. The results show an average score for the 10 assessed indicators (over a maximum of 4 points) of 2.3 for Chile and 2.2 for Uruguay, and an achievement level of 56.28% and 54.89%, respectively. These results provide a basis to guide public policy of both countries to strengthen the inclusion and treatment of DCT in initial teacher training. © 2019 Education Policy Analysis Archives. All rights reserved.